Preliminary trial of dorada fattening (Brycon moorei Steindachner 1878) in two stocking densities (Orinoquia, 2014)
Dorada is a native fish of the Magdalena River and have good husbandry characteristics; despite these potential, few data have been published on captive management. This study aimed to evaluate the effect of two stocking densities on zootechnical parameters of dorada, using a commercial diet. For this a total of 7200 doradas of initial average weight 8 ± 0.5 g and 5 ± 1 cm of total length, was stocking in six ear then ponds of 800 m2with two treatments: T1 (1fish / m2) and T2 (2 fish / m2); daily growth (DG), weight gain (G) feed conversion (FC) and survival (% S) was evaluated. The water quality parameters, dissolved oxygen (DO mg / L), pH, temperature (T°C), alkalinity (Alk), hardness (Dz) (mg / L CaCO3) and total ammonium (mg / L NH3) were registered. A commercial concentrate starting with 38% crude protein (% CP) along the first month was used; 30% CP in these cond month and ending with 25% CP until day 80 follow-up. Analyses of water quality remained stable during the culture period: OD (6.5 ± 1.2 mg / L), pH (6 ± 1.4), T (24 ± 1.5 °C), Alk-Dz (17.8 mg CaCO3 / L) and total NH3 (0.002 mg / L). The results of zootechnical parameters were: weight and total length for T1 281.48 ± 36 g and 26.01 ± 1.06 cm, respectively; T2 298.17 ± 27 g and 26.2 ± 1.1 cm; gain period 273 g and 290 g in T1 and T2 respectively; Daily growth 3.41 gfor T1 and 3.6 g for T2. Feed conversion 1.17 and 1.01 for T1 and T2. The survival was 98% in both treatments; differences between treatments were not significant (p> 0.05). It can be concluded that stocking density did not affect the measured zootechnical parameters, however T2 performed better.
Keywords: growth; bryconinae; density